2015
DOI: 10.1248/cpb.c15-00508
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2,7-Substituted (<i>S</i>)-1,2,3,4-Tetrahydroisoquinoline-3-carboxylic Acids: Peroxisome Proliferator-Activated Receptor γ Partial Agonists with Protein–Tyrosine Phosphatase 1B Inhibition

Abstract: A novel series of 2,7-substituted 1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid derivatives were synthesized and biologically evaluated. (S)-2-(2-Furylacryloyl)-7-[2-(2-methylindane-2-yl)-5-methyloxazol-4-yl] methoxy-1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid tert-butylamine salt (13jE) was identified as a potent human peroxisome proliferator-activated receptor γ (PPARγ)-selective agonist (EC 50 85 nM) and human protein-tyrosine phosphatase 1B (PTP-1B) inhibitor (IC 50 1.0 µM). Compound 13jE partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…We previously reported various types of PPARγ agonists using the same scaffold, 1,2,3,4-tetrahydroisoquinoline 3-calboxylic acid: a selective PPARγ full agonist, PPARγ full agonist with protein tyrosine phosphatase 1B (PTP1B) inhibition, PPARα/γ dual agonist with PTP1B inhibition, and PPARγ partial agonist with PTP1B inhibition. 25,26,[29][30][31] PTP1B negatively regulates the insulin signal and its overexpression has been implicated in insulin resistance; thus, the inhibition of PTP1B is expected to exert synergistic effects with PPARγ activation on insulin sensitization. [32][33][34] One of the 1,2,3,4-tetrahydroisoquinoline 3-calboxylic acids with PPARα/γ agonist and PTP1B inhibitory activities has been reported to exhibit effective antidiabetic activities with high safety, 35) and this may be due to its weak PPARγ activation and PTP1B inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported various types of PPARγ agonists using the same scaffold, 1,2,3,4-tetrahydroisoquinoline 3-calboxylic acid: a selective PPARγ full agonist, PPARγ full agonist with protein tyrosine phosphatase 1B (PTP1B) inhibition, PPARα/γ dual agonist with PTP1B inhibition, and PPARγ partial agonist with PTP1B inhibition. 25,26,[29][30][31] PTP1B negatively regulates the insulin signal and its overexpression has been implicated in insulin resistance; thus, the inhibition of PTP1B is expected to exert synergistic effects with PPARγ activation on insulin sensitization. [32][33][34] One of the 1,2,3,4-tetrahydroisoquinoline 3-calboxylic acids with PPARα/γ agonist and PTP1B inhibitory activities has been reported to exhibit effective antidiabetic activities with high safety, 35) and this may be due to its weak PPARγ activation and PTP1B inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported various 3-carboxyl-tetrahydroisoquinoline derivatives with PPARγ agonist activities ( Fig. 1): a 2-alkyl-3-carboxyl-7-phenyloxazolyl-tetrahydroisoquinoline derivative with PPARγ full agonist activity, 37) a 2-acyl-3-carboxyl-7-alkenyloxazolyl-tetrahydroisoquinoline derivative with PPARγ full agonist activity and PTP1B inhibition (KY-699), 16) a 2-acyl-3-carboxyl-7-cycloalkenyloxazol-tetrahydroisoquinoline derivative with PPARγ and PPARα dual agonist activity and PTP1B inhibition (KY-601), 15) and a 2-acyl-3-carboxyl-7-(bulky substituent) oxazolyl-tetrahydroisoquinoline derivative with partial PPARγ agonist activity and PTP1B inhibition (KY-755). 17) In these studies, we found that substituents on the oxazole influenced PPARγ agonist activity, and an aliphatic substituent was preferable for PTP1B inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a novel series of 2-acyl-3-carboxyl-tetrahydroisoquinoline derivatives with potent PPARγ activation and weak PTP1B inhibition. [14][15][16][17] However, even weak PPARγ activation may cause side effects in PPARγ agonist-sensitive patients.…”
mentioning
confidence: 99%
“…13) We previously demonstrated that a series of 3-carboxyl tetrahydroisoquinoline derivatives exhibited PPARγ agonist activities and weak PTP1B inhibitory activities. [14][15][16][17] Carboxyl types of inhibitors appear to compete with the substrate at the catalytic site, resulting in relatively low PTP1B selectivity because the catalytic site is similar among PTPs. 11,18) Although JTT-551 with a carboxyl moiety exhibited modest activity and antidiabetic effects in diabetic mice, clinical development was suspended possibly due to low efficacy in patients.…”
mentioning
confidence: 99%